Human Dimensions of Hurricane Floyd - Montz, Burrell Elizabeth (My University, 2009)
The panelists for this presentation are Dr. Jimmy Tickel, Catherine Smith, and Charles Fisher. Moderated by Dr. Burrell Montz. Dr. Montz, introduced herself and the panelists. She emphasized that even as we increase capacities, we learn from each natural disaster event. The panel represents a diversity of fields in the human dimensions of natural disaster research and spoke about the lessons learned.
Keywords: Hurricane Floyd, 1999; Hurricane workshops; Natural disasters